Characteristics of Carbonaceous Materials Synthesized from Palm Oil Empty Fruit Bunch Waste Using Ferrocene Catalyst - Shahab, Ahmad Nabil; Islam, Adinda Izzatul; Wardana, Afif; Yahya, Ilham Nur Dimas; Amalia, Ary Yanuar Tri; Sofyan, Nofrijon; Dhaneswara, Donanta (UI Scholars Hub, 2025)
The synthesis of carbonaceous materials for reduced graphene oxide (rGO) precursors using oil palm empty fruit bunches waste as a carbon source offers a sustainable solution for waste management in the palm oil industry while delivering high-performance materials. The oil palm empty fruit bunches were carbonized, followed by acid washing, pyrolysis with ferrocene (8%, 12%, and 16% variations), and ultrasonication to produce rGO. The structural, electronic, and morphological properties of the rGO were analyzed using various characterization techniques. The band gap values decreased with increasing ferrocene concentration, from 1.14 eV (8%) to 1.06 (16%), indicating enhanced electronic conductivity. XRD analysis revealed a crystal size increase from 11.3 nm (8%) to 181 nm (16%), while Raman spectroscopy showed a consistent D to G intensity ratio of 0.85, indicating reduced structural defects. SEM-EDS results demonstrated a carbon to oxygen atomic ratio of 4.38 (8%), 3.79 (12%), and 3.77 (16%), confirming successful reduction and improved carbon content. These finding highlight the potential of rGO synthesized from oil palm empty fruit bunches for applications in semiconductors, energy storage, and gas sensing, offering an innovative approach to sustainable materials development.